THE INFLUENCE OF ENTREPRENEURS ORIENTATION AND PRODUCT INOVATION ON COMPETITIVE ADVANTAGE OF CULINARY MSMEs IN BANDUNG CITY - Ayu Fadhila M, Sekar; Kaniawati, Keni (Universitas Pasundan, 2024)
The aim of this research is to find out the condition of Entrepreneurship Orientation, Product Innovation and Competitive Advantage of Culinary MSMEs in the City of Bandung. Also to determine the influence of Entrepreneurial Orientation and Product Innovation on the Competitive Advantage of Culinary MSMEs in Bandung City, either partially or simultaneously. The respondents involved in this research were a hundred Culinary MSMEs in the city of Bandung. The method used to collect samples is a non-probability sampling technique. Data collection was done with the aid of distributing questionnaires online and the information evaluation method was achieved using multiple linear regression. The results of this research show that partially Entrepreneurial Orientation and Product Innovation have a positive effect on the Competitive Advantage of Culinary MSMEs in the City of Bandung. Then, based on the results of the F test, it shows that Entrepreneurial Orientation and Product Innovation simultaneously influence the Competitive Advantage of Culinary MSMEs in the city of Bandung.